Bioabsorbable scaffolds for the treatment of obstructive coronary artery disease: the next revolution in coronary intervention?. Issue 17 (8th March 2013) - Patel, Niket; Banning, Adrian P
Abstract : Conventional drug eluting stents allow predictable long-term relief from coronary obstruction in most cases. However, rigid permanent metallic stents alter flow dynamics, abolish vascular reactivity, limit the potential for maximal vasodilation and promote ongoing inflammation and abnormalities of endothelial function. It is hypothesised that they may contribute to mal-apposition of stent struts, accelerated atheroma within the stented segment and perhaps very late stent thrombosis. Dramatic advances in bioabsorbable materials and technology have delivered the potential for a fully absorbable scaffold, which is able to mechanically support the coronary artery, and elute a drug, for a predetermined time period and is then fully absorbed in to the vascular wall. This could permit the 'normalisation' of vascular function, with a number of potential advantages including true normalisation of vasomotor function, restoration of physiological responses to stress/exercise and completion of the vascular response to stenting, without the long-term consequences related to inflammation, accelerated atherosclerosis and thrombosis. Currently, over 16 different scaffolds are at varying stages of development. This review summarises the rationale for the development of absorbable scaffolds and the principal clinical research data.